Andrografolid : Potensi Sebagai Antiaterosklerosis Pada Sitokin Il-1β - Putu Yudha Ugrasena; Iwan Saka Nugraha; Ni Wayan Rika Kumara Dewi (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
The focus is how the role of cytokines in atherosclerosis as a chronic inflammatory disease, as it is known that cytokines regulate complex inflammatory responses in atherosclerotic plaques, especially IL-1β. Sambiloto (Andrographis paniculata) is a plant with various pharmacological activities. Andrographolide (AND) is the main bioactive compound in the diterpene lactone group. This literature study aims to assess the potential of AND on the proinflammatory cytokine IL-1 β as an antiatherosclerosis. This type of research is a qualitative review of various studies using sambiloto plants or andrographolide compounds (AND). Search literature using the Google Scholar database. Keywords used